Clinical and pharmacoeconomic evaluation of antifungal prophylaxis with continuous micafungin in patients undergoing allogeneic stem cell transplantation: A six‐year cohort analysis. Issue 4 (6th January 2021) - Wingen‐Heimann, Sebastian M.; Cornely, Oliver A.; Vehreschild, Maria J.G.T.; Wisplinghoff, Hilmar; Franke, Bernd; Schons, Max; von Bergwelt‐Baildon, Michael; Scheid, Christof; Vehreschild, Jörg Janne
Abstract: Background: Patients undergoing allogeneic stem cell transplantation (aSCT) are at high risk to develop an invasive fungal disease (IFD). Optimisation of antifungal prophylaxis strategies may improve patient outcomes and reduce treatment costs. Objectives: To analyse the clinical and economical impact of using continuous micafungin as antifungal prophylaxis. Patients/Methods: We performed a single‐centre evaluation comparing patients who received either oral posaconazole with micafungin as intravenous bridging as required (POS‐MIC) to patients who received only micafungin (MIC) as antifungal prophylaxis after aSCT. Epidemiological, clinical and direct treatment cost data extracted from the Cologne Cohort of Neutropenic Patients (CoCoNut) were analysed. Results: Three hundred and thirteen patients (97 and 216 patients in the POS‐MIC and MIC groups, respectively) were included into the analysis. In the POS‐MIC and MIC groups, median overall length of stay was 42 days (IQR: 35–52 days) vs 40 days (IQR: 35–49 days; p = .296), resulting in median overall costs of €42, 964 (IQR: €35, 040–€56, 348) vs €43, 291 (IQR: €37, 281 vs €51, 848; p = .993), respectively. Probable/proven IFD in the POS‐MIC and MIC groups occurred in 5 patients (5%) vs 3 patients (1%; p = .051), respectively. The Kaplan‐Meier analysis showed improved outcome of patients in the MIC group at day 100 ( p = .037) and day 365 ( p < .001) following aSCT. Conclusions: Our study results demonstrate improved outcomes in the MIC group compared with the POS‐MIC group, which can in part be explained by a tendency towards less probable/proven IFD. Higher drug acquisition costs of micafungin did not translate into higher overall costs.